Cultural diversity and public administration in Jordan - Alhrout, Ahmad (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to present the cultural diversity and public administration in Jordan. The Hashemite Kingdom of Jordan is a monarchy. Its legal order is based on the provisions of the Constitution of January 1, 1952. Because of the nature of its cultural and demographic diversity, the Kingdom has been affected in terms of legal sovereignty. The legal system of the country is characterized as a mixed legal system between civil and Sharia law with the classical separation of powers.
Keywords: culture; public administration; the Hashemite Kingdom of Jordan; diversity